Levels of CEACAM6 in Peripheral Blood Are Elevated in Patients with Plasma Cell Disorders: A Potential New Diagnostic Marker and a New Therapeutic Target?. (27th January 2019) - Steiner, N.; Hajek, R.; Nachbaur, D.; Borjan, B.; Sevcikova, S.; Göbel, G.; Gunsilius, E.
Abstract : Introduction . The prognosis of multiple myeloma is still unfavorable due to inherent characteristics of the disease and the often-delayed diagnosis due to widespread and unspecific symptoms such as back pain and fatigue. Therefore, a simple diagnostic blood test would be helpful to speed up the diagnostic procedure in such patients (pts.). Here, we evaluated the diagnostic value of plasma levels of carcinoembryonic antigen-related cell adhesion molecule 6 (CEACAM6) in the peripheral blood and bone marrow of pts. with plasma cell disorders and in healthy controls. Materials and Methods . Immunoreactive CEACAM6 was determined in the peripheral blood and bone marrow (n = 95 / 100 ) of pts. with monoclonal gammopathy of unknown significance (MGUS: 28/37), newly diagnosed multiple myeloma (NDMM: 42/40), and relapsed/refractory multiple myeloma (RRMM: 25/23) by sandwich ELISA. Results . Median CEACAM6 levels in the peripheral blood of pts. with plasma cell disorders were significantly higher than those of healthy controls (healthy controls: 15.2 pg/ml (12.1-17.1); MGUS: 19.0 pg/ml (16.4-22.5); NDMM: 18.0 pg/ml (13.4-21.2); and RRMM: 18.9 pg/ml (15.2-21.5);p < 0.001 ). Plasma levels of CEACAM6 discriminated healthy subjects from MGUS/NDMM pts. (A U C = 0.71, 95% CI: 0.6-0.8); i.e., a CEACAM6l e v e l > 17.3 pg/ml has an 82% (95% CI: 70-90) predictive probability for the identification of MGUS or NDMM. Moreover, CEACAM6 levels in the bone marrow were significantly higher in RRMM pts. than in NDMM pts. (p = 0.04 ), suggesting a role of this molecule in disease progression. Conclusion . CEACAM6 plasma levels can noninvasively identify pts. with a plasma cell disorder and should be evaluated prospectively as a potential diagnostic marker. Moreover, due to high CEACAM6 levels in the bone marrow in RRMM pts., this adhesion molecule might be a therapeutic target in multiple myeloma pts.